2020
DOI: 10.1007/s00066-020-01598-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies to prevent and reduce gynecomastia and/or breast pain caused by antiandrogen therapy for prostate cancer

Abstract: Aim To provide an overview on the available treatments to prevent and reduce gynecomastia and/or breast pain caused by antiandrogen therapy for prostate cancer. Methods The German Society of Radiation Oncology (DEGRO) expert panel summarized available evidence published and assessed the validity of the information on efficacy and treatment-related toxicity. Results Eight randomized controlled trials and one meta-analysis were identified. Two randomized trials demonstrated that prophylactic radiation therapy (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
5
0
5
Order By: Relevance
“…In this regard, a meta-analysis has shown that prophylactic radiotherapy, as well as daily tamoxifen, can significantly reduce the incidence of gynaecomastia and/or breast pain and therefore, one of these strategies should be considered in future studies. Also, the authors concluded that tamoxifen appears to be an effective alternative to radiotherapy as a therapeutic treatment in the presence of gynaecomastia, but its side effects and off-label use must be considered [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a meta-analysis has shown that prophylactic radiotherapy, as well as daily tamoxifen, can significantly reduce the incidence of gynaecomastia and/or breast pain and therefore, one of these strategies should be considered in future studies. Also, the authors concluded that tamoxifen appears to be an effective alternative to radiotherapy as a therapeutic treatment in the presence of gynaecomastia, but its side effects and off-label use must be considered [21].…”
Section: Discussionmentioning
confidence: 99%
“…Enzalutamide, an androgen receptor signaling inhibitor was shown to be associated with a 49% rate of gynecomastia within 2 years. Tamoxifen has been used as drug intervention to block the ERα in breast tissues and the data from 8 clinical randomized trials revealed that tamoxifen is well tolerated by PCa patients[41].…”
Section: Discussionmentioning
confidence: 99%
“…Chez le patient présentant une contreindication au traitement par le tamoxifène, la radiothérapie est l' option de choix, l'avantage étant la courte durée du traitement. Par contre, les patients devraient être informés d'une possible cardiotoxicité [15][16][17]. En revanche, elle devrait être évitée chez le patient jeune au vu du risque de développement d'un cancer mammaire secondaire [18].…”
Section: Traitementunclassified